Issue Information. (8th March 2021) - Unknown
Abstract : Cover Photograph: Top left: Chromosome compartments on the autosomes and the inactive X chromosome in mammals (see Poonperm & Hiratani, pp. 5‐17). Top middle: The outline of the neural differentiation and representative signal molecules involved in each differentiation step (see Sasai et al., pp. 26‐37). Top right: Schematic presentation of liver bud formation (see Thompson & Takebe, pp. 47‐58). 2nd middle: Human iPSC‐derived cartilage (see Yamashita & Tsumaki, pp. 72‐81). 3rd left: Modeling human paraxial mesoderm patterning in vitro using human iPSCs (see Nakajima & Ikeya, pp. 38‐46). 3rd middle: Regionalization in the central nervous system and its recapitulation with PSC‐derived neural cells (see Imaizumi & Okano, pp. 18‐25). 3rd right: Host‐graft synapse formation using an iPSC‐retina transplant in a retinal degeneration model mouse (see Uyama et al., pp. 59‐71).